2018
DOI: 10.1016/j.stueduc.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Learning to teach: Effects of classroom observation, assignment of appropriate lesson preparation templates and stage focused feedback

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The established stage-order overlaps with those reported in research into teacher development (Berliner, 2004;Fuller, 1969;Huberman, 1993) and provides a means to link the teacher's performance score back to specific teaching practices associated with that stage of development. It has been shown that using these stage models to scaffold feedback and coaching has medium to large effects on development of teaching quality (Tas, Houtveen, Van de Grift, & Willemsen, 2018) and may outperform feedback and coaching methods not based on the stages (Antoniou & Kyriakides, 2011). Furthermore, both student surveys and classroom observations have been proven valid measures to identify teachers' stage of development (Maulana & Helms-Lorenz, 2016;Van de Grift et al, 2014;Van der Lans et al, 2015, 2017, 2018).…”
mentioning
confidence: 99%
“…The established stage-order overlaps with those reported in research into teacher development (Berliner, 2004;Fuller, 1969;Huberman, 1993) and provides a means to link the teacher's performance score back to specific teaching practices associated with that stage of development. It has been shown that using these stage models to scaffold feedback and coaching has medium to large effects on development of teaching quality (Tas, Houtveen, Van de Grift, & Willemsen, 2018) and may outperform feedback and coaching methods not based on the stages (Antoniou & Kyriakides, 2011). Furthermore, both student surveys and classroom observations have been proven valid measures to identify teachers' stage of development (Maulana & Helms-Lorenz, 2016;Van de Grift et al, 2014;Van der Lans et al, 2015, 2017, 2018).…”
mentioning
confidence: 99%
“…A previous study with a quasi-experimental design showed that student teachers (n ¼ 135) (trained with classroom observation, the assignment of an appropriate lesson template, mentor feedback and additional theoretical meetings linking theory to student teachers practice) achieved a higher level in teaching compared to student teachers in the (rather small) control group (n ¼ 63) that where not trained in this way (Tas et al, 2018). The student teachers in the experimental group showed in the six domains of the ICALT observation instrument a growth of an effect size between 0.81 and 1.12, which is a large growth.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Educating student teachers is a shared responsibility between the teacher training college and the internship school. Although a close collaboration within this teacher training community is considered an important prerequisite for a much-desired improvement of the quality of teaching (Ministry of Education, 2019), the training partners still operate in relative isolation, pursuing their own training objectives and own agenda’s, according to their own views on what is good teaching and effective training (Valencia et al , 2009; Tas et al , 2018).…”
Section: Introduction and Research Questionmentioning
confidence: 99%
“…For unexperienced PSTs achieving all aspects of effective teaching during their first practical experiences in schools is demanding. Research has proposed that PSTs' teaching skill development should start with the basic tasks of lesson planning and providing clear instructions (i.e., including objectives and clear structures) before working on more advanced tasks such as making use of higherorder thinking techniques for students' cognitive activation (Fuller & Bown, 1975;Tas, Houtveen, van de Grift, & Willemsen, 2018). Simulating cognitive activation requires PSTs to have the capacity to focus on students' individual learning needs (Baumert et al, 2010;Tas et al, 2018).…”
Section: Meta-analysis On Coaching Mentoring Supervision Effects Onmentioning
confidence: 99%
“…Feedback consists of information about the PSTs' skills during the learning process and how they can develop these skills in future practice (Hattie & Timperley, 2007;Thurlings, Vermeulen, Bastiaens, & Stijnen, 2013). Recent research suggested that more structured observation based on observation tools can be helpful to provide more systematic feedback on PSTs' teaching practices (Tas et al, 2018). The feedback of CTs can be used by PSTs after the lesson to improve future lesson plans and lessons.…”
Section: Learning Opportunities During Post-lesson Conferencesmentioning
confidence: 99%